A Cisplatin‐Selective Fluorescent Probe for Real‐Time Monitoring of Mitochondrial Platinum Accumulation in Living Cells. (2nd February 2021) - Ong, Jun Xiang; Le, Hai Van; Lee, Violet Eng Yee; Ang, Wee Han
Abstract: Mitochondria have emerged as important targets for cisplatin in cancer therapy. Apart from cisplatin, anticancer Pt complexes based on similar scaffolds have also been developed to target mitochondria. Yet cellular processing of cisplatin or these mitochondria‐targeting Pt analogues remained unexplored, largely due to a lack of tools capable of probing these Pt drugs within an intracellular environment. We developed the first mitochondria‐targeted fluorescent probe for real‐time monitoring of Pt accumulation in mitochondria. We applied the probe to investigate mitochondria as cellular targets for Pt drug complexes and uncovered two distinct pathways whereby these Pt complexes could be delivered to mitochondria after cell entry. Abstract : Real‐time cisplatin trafficking: A mitochondria‐targeting fluorescent probe was engineered to detect the clinically‐important platinum drug cisplatin in real‐time. The probe was applied to investigate the mitochondria as cellular targets for cisplatin and its analogues. Two distinct pathways whereby Pt complexes could be delivered to mitochondria after cell entry were uncovered.